Extracellular RNA drives TNF-a/TNF-receptor-1 mediated cardiac ischemia/reperfusion injury: Mechanistic insights and therapeutic potential of RNase1 - Cabrera-Fuentes, Hector A.; Ruiz-Meana, Marisol; Barreto, Guillermo; Serebruany, Victor L.; Sánchez-Vega, Jose T.; Pérez-Campos, Eduardo; Kostin, Sawa; Böning, Andreas; Jarquín González, Efrén Emmanuel; Al-Suhaimi, Ebtesam A.; Rodriguez-Montesinos, Julian; Inserte, Javier; et al. (My University, 2025)
Myocardial ischemia/reperfusion (I/R) injury causes cardiomyocyte death and exacerbates inflammation. Emerging evidence implicates extracellular RNA (eRNA) and tumor necrosis factor-α (TNF-α) as key mediators. We hypothesize that eRNA released from ischemic cardiomyocytes amplifies I/R injury via TNF-α/TNF-receptor- 1 (TNF-R1) signaling, and that hydrolysis of eRNA by RNase1 can attenuate I/R injury by disrupting this pathway. Here, we investigated the mechanistic role of eRNA and its interplay with TNF-α signaling in cardiac I/ R injury, and evaluated the therapeutic potential of RNase1 and cyclosporine-A (CsA). In ST-segment elevation myocardial infarction patients, plasma eRNA levels were significantly elevated 2 h post-percutaneous coronary intervention (PCI), correlating positively with Creatine Kinase (CK). In murine I/R and hypoxia/reoxygenation models, eRNA released from stressed cardiomyocytes acted as a damage-associated molecular pattern, triggering TNF-α shedding via TACE/ADAM17 and activating TNF-R1-mediated inflammation, mPTP opening, and cell death. Genetic deletion of TNF-α or TNF-R1 abrogated eRNA-induced cytotoxicity, while TNF-receptor- 2 (TNF- R2) deficiency exacerbated injury. Pharmacological inhibition of TACE with TAPI suppressed TNF-α release and preserved cell viability. RNase1 effectively degraded eRNA, blocking upstream pro-inflammatory signaling, whereas CsA preserved mitochondrial integrity by preventing mPTP opening. Notably, RNase1 and CsA showed synergistic protection in vivo when administered at reperfusion, significantly reducing myocardial infarct size. These findings identify eRNA as both a biomarker and pathogenic mediator of myocardial I/R injury, and support a dual-targeted strategy using RNase1 and CsA to interrupt the TNF-α/TNF-R1-driven inflammatory and mito chondrial death pathways. Targeting both upstream inflammatory and downstream mitochondrial mechanisms represents a promising cardioprotective intervention for acute myocardial infarction.
Keywords: ddc:610